Lobetyolin protects mice against LPS-induced sepsis by downregulating the production of inflammatory cytokines in macrophage - Chen, Zhonghua; Su, Yixin; Ding, Jingtong; He, Jia; Lai, Lihua; Song, Yinjing (Frontiers in Pharmacology, 2024)
Sepsis is a clinical syndrome characterized by dysregulation of the host immune response due to infection, resulting in life-threatening organ damage. Despite active promotion and implementation of early preventative measures and bundle treatments, sepsis continues to exhibit high morbidity and mortality rates with no optimal pharmacological intervention available. Lobetyolin (LBT), the crucial component of polyacetylenes found in Codonopsis pilosula, has been scientifically proven to possess potent antioxidant and antitumor properties. However, its therapeutic potential for sepsis remains unknown. In this study, we observed a significant increase in the survival rate of mice pretreated with LBT in a lipopolysaccharide (LPS) induced sepsis mouse model. LBT demonstrated a remarkable reduction in the production of IL-6, TNF-α, and IL-1β in the serum, along with mitigated lung and liver tissue damage characterized by reduced inflammatory cell infiltration.Additionally, through RNA-seq analysis coupled with GO and KEGG analysis, it was revealed that LBT effectively suppressed genes associated with bacterium presence, cellular response to lipopolysaccharide stimulation, as well as cytokine-cytokine receptor interaction involving Cxcl10, Tgtp1, Gbp5, Tnf, Il1b and IRF7 specifically within macrophages. We also confirmed that LBT significantly downregulates the expression of IL-6, TNF-α, and IL-1β in macrophage activation induced by LPS. Therefore, our findings demonstrated that LBT effectively inhibits the production of inflammatory cytokines (IL-6, TNF-α, and IL-1β) and mitigates sepsis induced by LPS through modulating macrophages' ability to generate these cytokines. These results suggest that LBT holds promise as a potential therapeutic agent for sepsis treatment.